Socio-scientific issues in science education: Contexts for the promotion of key learning outcomes - Sadler, T.; Dawson, Vaille (Springer, 2012)
Science education scholars and practitioners have called for the contextualization of science content through the exploration of socially relevant issues, also known as socio-scientific issues (SSI), throughout the field’s history. In this chapter we explore the effectiveness of SSI as contexts for science education. Specifically, we review studies that empirically test the effects of SSI-based curricula on the following learning outcomes: science content knowledge, nature of science, interest and motivation, and argumentation. The results provide evidence of positive effects of SSI-based curricula on student learning and practices related to all of the aforementioned areas. We conclude that the research base supports integration of SSI in school science education.